2012
DOI: 10.1007/s00421-012-2559-6
|View full text |Cite
|
Sign up to set email alerts
|

Muscle–tendon interaction and EMG profiles of world class endurance runners during hopping

Abstract: The present study examined the muscle-tendon interaction of ten international level Kenyan runners. Ultrasonography and kinematics were applied together with EMG recordings of lower limb muscles during repetitive hopping performed at maximal level. The ten Kenyans had longer gastro Achilles tendon at rest (p < 0.01) as compared with ten control subjects matched in height. Conversely, the stretching and shortening amplitudes of the tendinous tissues of the medial gastrocnemius (MG) muscle were significantly sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 23 publications
5
31
1
1
Order By: Relevance
“…It has been demonstrated both computationally (Ettema, 2001;Lichtwark and Wilson, 2005) and experimentally (Hoffrén et al, 2012;Sano et al, 2013) that tendons with different mechanical properties may require different muscle activation strategies to achieve similar levels of efficiency. Moreover, previous studies have shown lower agonist and higher antagonist muscle activities in pre-pubertal children than in postpubertal children and adults (Lloyd et al, 2012) during the preactivation, braking and propulsive phases of jumping activities.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated both computationally (Ettema, 2001;Lichtwark and Wilson, 2005) and experimentally (Hoffrén et al, 2012;Sano et al, 2013) that tendons with different mechanical properties may require different muscle activation strategies to achieve similar levels of efficiency. Moreover, previous studies have shown lower agonist and higher antagonist muscle activities in pre-pubertal children than in postpubertal children and adults (Lloyd et al, 2012) during the preactivation, braking and propulsive phases of jumping activities.…”
Section: Discussionmentioning
confidence: 99%
“…1). In addition, the East-Africans showed smaller tendon stretching (strain) and shortening during hopping exercises 13) (Fig. 2) data).…”
Section: Textmentioning
confidence: 86%
“…Recently, some authors reported specific anatomical properties such as greater tendon length of the lower limbs in Afro-Caribbean subjects compared to Caucasian subjects (Kunimasa et al, 2014; Sano et al, 2013). Indeed, the greater tendon length may positively contribute to the output from the muscle tendon complex in a stretch shortening cycle during jumping with prestretch and this feature could be responsible for better vertical jump performance in the Afro-Caribbean participants.…”
Section: Discussionmentioning
confidence: 99%